On the occurrence and toxicity of Cylindrospermopsis raciborskii in Poland - Rzymski Piotr; Brygider Agnieszka; Kokociński Mikołaj (Limnological Review, 2017)
Cylindrospermopsis raciborskii which belongs to the order of Nostocales has continuously been at the centre of interest of various research groups owing to its great ecological plasticity, wide distribution and potential to produce different metabolites known to be harmful for humans and animals. Over recent decades, Polish strains of C. raciborskii have also been studied with regard to these issues. The present paper is a brief review of the present state of knowledge respecting the occurrence and toxicity of this species with emphasis on Polish strains, and indicates potential directions for future research.